2008
DOI: 10.1002/j.0022-0337.2008.72.11.tb04618.x
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Dental School Applicants and Enrollees, 2006 and 2007 Entering Classes

Abstract: The number of applicants to dental schools in the United States continues to rise at a double-digit rate, 12 percent from 2005 to 2006 and 14 percent from 2006 to 2007. The number of applicants to the 2006 and 2007 years' entering classes of U.S. dental schools was 12,500 and 13,700, respectively. The number of first-time enrollees (4,600) in 2007 was the highest recorded since 1989. Men continue to comprise the majority of all applicants, 55 percent in 2006 and 53 percent in 2007. However, the percentage of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Thirty‐eight percent of the first‐year students who took the baseline survey in our study were female. In the mid‐1980s female dental school entrants comprised 19.8 percent of the total, but in 1990 the number rose to 38 percent and in 2006 it was up to 43.4 percent 33. This consistent increase in the resulting proportion of women dentists may bode well for underserved populations if the gender differences found in our study are replicated by others.…”
Section: Discussionsupporting
confidence: 65%
“…Thirty‐eight percent of the first‐year students who took the baseline survey in our study were female. In the mid‐1980s female dental school entrants comprised 19.8 percent of the total, but in 1990 the number rose to 38 percent and in 2006 it was up to 43.4 percent 33. This consistent increase in the resulting proportion of women dentists may bode well for underserved populations if the gender differences found in our study are replicated by others.…”
Section: Discussionsupporting
confidence: 65%
“…The 2008 data on applicants to medical schools lists the percentage of female applicants at 48 percent (N = 20,360), with males at 52 percent (N = 21,870) (AAMC 2008). For dental schools, the majority of applicants (57 percent) were male (Okwuje et al 2008).…”
mentioning
confidence: 99%
“…It is encouraging that multiple studies have now confirmed the improvement in gender equity. The increase in female enrollment could be due to an increased need for orthodontists to meet patient demands 35 and/or a corresponding increase in female predoctoral applicants and enrollment in dental schools 36 …”
Section: Discussionmentioning
confidence: 99%